2013
DOI: 10.1007/s00894-013-2048-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of alcohols with zeolite BEA and MOR frameworks

Abstract: Zeolites can adsorb small organic molecules such as alcohols from a fermentation broth. Also in the zeolite-catalyzed conversion of alcohols to biofuels, biochemicals, or gasoline, adsorption is the first step. Several studies have investigated the adsorption of alcohols in different zeolites experimentally, but computational investigations in this field have mostly been restricted to zeolite MFI. In this study, the adsorption of C1-C4 alcohols in BEA and MOR was investigated using density functional theory (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Methanol adsorption inside zeolites is a research topic on which several studies, both experimental and theoretical, have been reported in the literature. , In the papers mentioned above, attention was mainly focused on the interaction between the methanol and the zeolite acid site. The presence of two hydrogen bonds has been described, the first being medium to strong and the second being much weaker.…”
Section: Resultsmentioning
confidence: 99%
“…Methanol adsorption inside zeolites is a research topic on which several studies, both experimental and theoretical, have been reported in the literature. , In the papers mentioned above, attention was mainly focused on the interaction between the methanol and the zeolite acid site. The presence of two hydrogen bonds has been described, the first being medium to strong and the second being much weaker.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster investigations, up to the MP2 level, conclude that methoxonium does not constitute the local energy minimum for methanol, consistently with NMR spectra recorded for the H-Rho zeolite . However, the shape of the potential energy surface was shown to depend on the level of theory, on the type of zeolite model, on the zeolite framework, on the position of the Brønsted acid site, and on the alcohol under consideration. The proton affinity of the alcohol, itself a function of the degree of substitution of the alcohol, was shown to be a relevant parameter to quantify its propensity toward protonation by the zeolite . Methanol in ferrierite at 300 K, ethanol, and 1-propanol in H-ZSM-5 close to 500 K, were shown by AIMD to be easily protonated.…”
Section: Dehydration Of Alcohols and Polyhydroxy Moleculesmentioning
confidence: 56%
“…We computed the adsorption energy of MeOH for various frameworks and obtained binding energies ranging from À 91 kJ/mol (H-SAPO-34) to À 119 kJ/mol (H-MOR and H-ZSM-22, see Table 1) in good agreement with earlier theoretical studies (see Table S4 for an in-depth comparison with data available in the literature). [36][37][38][39][40][41] The reaction of adsorbed MeOH with the acid site forming an SMS and water is computed to have reaction barriers ranging from 126 kJ/mol (H-SAPO-34) to 150 kJ/mol (H-BEA) when referenced to the adsorbed MeOH. We calculated the analogous reaction of ethanol (EtOH) with the acid site producing a surface ethoxy species (SES) for the eight acidic zeotypes considered herein as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction has been investigated theoretically to a great extend [30,36–41] as it constitutes the first step in stepwise (or dissociative) methylation reactions (e. g. stepwise formation of dimethyl ether (DME) via MeOH). We computed the adsorption energy of MeOH for various frameworks and obtained binding energies ranging from −91 kJ/mol (H‐SAPO‐34) to −119 kJ/mol (H‐MOR and H‐ZSM‐22, see Table 1) in good agreement with earlier theoretical studies (see Table S4 for an in‐depth comparison with data available in the literature) [36–41] . The reaction of adsorbed MeOH with the acid site forming an SMS and water is computed to have reaction barriers ranging from 126 kJ/mol (H‐SAPO‐34) to 150 kJ/mol (H‐BEA) when referenced to the adsorbed MeOH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation